2021
DOI: 10.1101/2021.11.03.21265823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Life after mild traumatic brain injury: Widespread structural brain changes associated with psychological distress revealed with multimodal magnetic resonance imaging

Abstract: BackgroundTraumatic brain injury (TBI) can alter brain structure and lead to onset of persistent neuropsychological symptoms. This study investigates the relationship between brain damage and psychological distress after mild TBI (mTBI) using multimodal magnetic resonance imaging (MRI).MethodsEighty-nine mTBI patients from the TRACK-TBI (Transforming Research and Clinical Knowledge in Traumatic Brain Injury) pilot study were included. Subscales of the Brief Symptoms Inventory 18 for depression, anxiety, and so… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…There are a few possibilities for the lack of meaningful mediation in our study. First, studies that have found significant structural MR changes after TBI often use very specific time ranges post injury to conduct the MRI scan, often occurring within 1 month of the injury (13,(56)(57)(58). Even within these studies, changing the time interval of MRI after injury resulted in different findings of GM and WM differences over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few possibilities for the lack of meaningful mediation in our study. First, studies that have found significant structural MR changes after TBI often use very specific time ranges post injury to conduct the MRI scan, often occurring within 1 month of the injury (13,(56)(57)(58). Even within these studies, changing the time interval of MRI after injury resulted in different findings of GM and WM differences over time.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the screener does not require a hospital or doctor visit to diagnose the injury, but solely relies on reported symptoms. In contrast, most studies conducted post-injury are using patients who report to a hospital or some medical professional shortly after the injury (13, 56-58). With this difference in inclusion criteria, the present study may be collecting a larger portion of mild injuries that have not been included in prior research and consequently have more mild or reduced brain changes.…”
Section: Discussionmentioning
confidence: 99%